The Hydrodynamics of Swan Estuary - Using a Numerical Approaches - Hajiani, M.; Sarukkalige, Priyantha (Research Publishing Services, 2012)
As the populations increase in coastal zones, the deterioration of water quality accelerates. Swan River Estuary, in Western Australia, has experienced considerable side effects from urbanization. As the interactions between the physical, chemical, and biological process in estuary are difficult so numerical models as a facilitator tools are applied to solve this complexity. They present a realistic view of hydrodynamics and water quality of a water body and illustrate the temporal and spatial variation of nutrients. To simulate hydrodynamics of Swan Estuary a laterally averaged two-dimensional model called CE-QUAL-W2 was applied. This model has been widely applied to stratified water systems such as lakes, reservoirs, and estuaries. Application of different algorithm for vertical eddy viscosity/diffusivity has increased model capability. The selected river area was divided to some elements with equal horizontal and vertical grid spacing. The upstream and downstream boundary conditions were applied. With optimizing the bottom friction factor, the best fit of the recorded and simulated water level curves of control station was obtained with the Manning Coefficient of 0.024. Salinity profiles were used to simulate the mixing processes. Model was executed with two different vertical eddy diffusivity formulations. Then the better algorithm was chosen. Model was applied for different conditions and it could reproduce the hydrodynamic of water body properly.